Impact of Addition of Tiger nut Tubers Flour on Chemical, Sensory and Nutritional Characteristics of Pan Bread - Gamal, S. El-Hadidy (Food Technology Research Journal, 2023)
In the present investigation, partial replacement of wheat flour (WF) with tiger nut tubers flour (TNTF) at extents of 10%, 20%, 30% and 40% were carried out to examine the chemical comprise and physical attributes of the product. The partial replacement of WF with TNTF raised the fat, fiber and ash (P≤0.05), while, the available carbohydrates and crude protein were reduced. Also, The addition of TNTF raised caloric value. Pan bread that had been fortified with TNTF had lower quality in terms of colour. With only a minor decline in bread quality, TNTF up to 40% could partially replace WF in pan bread and boost its nutritious value in terms of fiber and vital amino acids. When compared to the control, sensory characteristics showed that pan bread enriched with up to 40% TNTF was acceptable to the panelists and significantly different in terms of overall acceptability, crumb texture, appearance, crust colour, crumb grain, and flavor . When TNTF was added, the nutritional benefits and amino acid content were higher than in the control group (for pan bread).